2021
DOI: 10.1111/joim.13291
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent lipid profile inversely associates with mortality in hemodialysis patients – independent of inflammation/malnutrition

Abstract: Background Patients with end‐stage kidney disease have an extremely high cardiovascular mortality rate, but there is a paradoxical relationship between lipid profile and survival in haemodialysis patients. To investigate whether inflammation/malnutrition confounds the associations between lipids and mortality, we studied a full lipid profile comprising of five clinically well‐established lipid parameters and its associations with mortality in a large, multinational European cohort with a median follow‐up >3 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Elbert et al proved that a total cholesterol, HDL, non-HDL, and LDL level was associated with higher allcause, cardiovascular and non-cardiovascular mortality. In this study there was no correlation between mortality and an inflammation/malnutrition status for all lipid fractions (Ebert et al, 2021). Moreover, because of an enormous relationship between lipid serum profile and CVD risk, there is a need to find new diagnostic pathways which will improve the assessment of prognosis in dialysis patients.…”
Section: Lipid Abnormalities In Haemodialyzed Patientsmentioning
confidence: 56%
“…Elbert et al proved that a total cholesterol, HDL, non-HDL, and LDL level was associated with higher allcause, cardiovascular and non-cardiovascular mortality. In this study there was no correlation between mortality and an inflammation/malnutrition status for all lipid fractions (Ebert et al, 2021). Moreover, because of an enormous relationship between lipid serum profile and CVD risk, there is a need to find new diagnostic pathways which will improve the assessment of prognosis in dialysis patients.…”
Section: Lipid Abnormalities In Haemodialyzed Patientsmentioning
confidence: 56%
“…For example, the uremic toxin symmetric dimethylarginine was shown to accumulate in HDL cholesterol, modulating its function by inhibiting anti-inflammatory properties, and was associated with reduced reverse cholesterol efflux and increased mortality [18]. In accordance, our group recently demonstrated that lipid parameters are counterintuitively inversely associated with mortality in incident hemodialysis patients [19] suggesting a uremia-induced dysregulation of lipid profile.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, statin treatment does not affect uremic toxins' independent significant associations with lipid profile (i.e., IAA, TMAO, and PAG) in our tri-national cohort. Moreover, the ARO hemodialysis study has recently demonstrated an inverse relationship between lipid profile and mortality independent of the aforementioned covariates [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most lung transplant recipients have ESLD, and their complex conditions may lead to malnutrition (17). Malnutrition can increase the risk of respiratory infections, affect the immune system, and even worsen the function of respiratory muscles (18), which can affect the incidence of postoperative complications and mortality (19).…”
Section: Discussionmentioning
confidence: 99%